A Clinical Evaluation of a Multipurpose Soft Contact Lens Solution: Unicare - Callender, M G; Chan, A (Canadian Journal of Optometry, 1984)
A three-month study was conducted to establish the safety and efficacy of Unicare® - a multipurpose soft contact lens solution. Patient acceptance of the solution was good in spite of one case of an adverse ocular response among the twenty-one subjects evaluated.